A-292 Graph Theoretical Analysis of Brain Functional Connectivity in Initiation and Inhibition Tasks. (17th August 2022) - Davis, Alexandra
Abstract: Objective: Using graph theoretical analysis, the current study explores network properties of highly associated brain areas during initiation and inhibition. Method: The current study utilized a publicly available dataset of functional connectivity matrices generated during initiation and inhibition (go/nogo paradigm) in 144 healthy adults between the age of 20 and 86 who were recruited from the greater Toronto area (Jenny R Rieck et. al, 2021). The researcher selected brain areas (ROIs) that showed high correlation (>0.75) from each participant's matrices and input high incidents of functional connectivity among all participants into an incidental matrix which was used to generate a network graph for each task. ROIs are presented as nodes (vertices) while their connections are edges. Core measures, such as degree distribution, mean distance, within module degree z score, and gateway coefficient, were analyzed. Results: The analysis showed a disconnected network across several brain regions and several common connections among somatomotor, default A, and peripheral visual networks. For the initiation task, the medial prefrontal cortex on both hemispheres are more frequently activated. A high betweenness was found in different brain areas for the inhibition and initiation across visual and default networks. Further analysis showed the extra-striate cortex appears to be the "hub" for initiation while the extra-striate superior cortex appears to be the "hub" for inhibition. Conclusion(s): The present study showed several common brain areas that are activated during both initiation and inhibition, highlighted differences in activation between the two tasks and explored several areas that could be a "hub" during each task.